ANALYSIS OF BUSINESS AND ADDED VALUE OF COFFEE BUSINESS “KOPI KEPAHIANG” IN PASAR UJUNG VILLAGE KEPAHIANG DISTRICT - Helda Indra Yenti; Reflis; Bambang Sumantri1 (Journal of Agri Socio Economics and Business, 2023)
The purpose of this research is to analyze the supply chain, the business costs of making "Kopi Kepahiang" ground coffee, the added value of making "Kopi Kepahiang" ground coffee. The analytical method uses quantitative descriptive analysis. Research shows that the supply chain for the coffee making business "Kopi Kepahiang" consists of two patterns, namely the flow of products and the flow of money. Product Flow in Pattern I (Supplier-Kopi Kepahiang Business-Consumers), Pattern II (Supplier-Kopi Kepahiang Business-Resellers-Consumers). The flow of money in Pattern I (Supplier- Kopi Kepahiang Business--Consumers), Pattern II (Supplier-Kopi Kepahiang Business-Resellers-Consumers). The production processes for making coffee powder are: roasting, cooling, grinding and packaging. Cost of production of ground coffee business “Kopi Kepahiang” red pickled beans Rp. 25,198,977/8 months or Rp.14,867/package, while super-powdered coffee costs Rp.22,040,531/8 months or Rp.11,479/package. The net profit of the business of making ground coffee "Kopi Kepahiang" from red picking seeds is Rp. 25,641,332/8 months from super random seeds of Rp. 16,349,160/8 months. Break Even Point (BEP) for the business of making coffee "Kopi Kepahiang" from red pickled beans, namely a production volume of 183 packs with a value of Rp. 54,800, while BEP of super random ground coffee, a production volume of 322 packs with a value of Rp. 64,360. The added value obtained from the ground coffee business "Kopi Kepahiang" as raw material for red picking coffee is Rp.64,444 with an added value ratio of 56.18% and for super-origin ground coffee Rp.32,956 with a value ratio of 44.73%.